Factors associated with the mode of delivery in twin pregnancy in Hospital USM - Rosdi@Rosli, Nor Azlina (2016)
Background: The incidence of twin pregnancy has been increasing in trend. The mode of delivery in second stage can be either via spontaneous vaginal delivery, assisted vaginal delivery or by lower segment caesarean section. The presentation of the first twin will determine the type of delivery regardless the presentation of the second twin. Objective : The objective of this study was to determine the factors associated with the mode of delivery among twin pregnancy in Hospital USM. Methods: A cross sectional study was conducted for this study. Data of twin pregnancy were reviewed from medical record department in Hospital USM from 1st of January 2010 until 31st December 2015. The inclusion criterias were live births for both babies, delivered more than 24 weeks of gestational age and baby weight more than 500 grams. Babies with severe fetal malformation or in utero fetal death were excluded. Proforma was used during data collection to reduce bias. Multinomial Logistic Regression was applied for statistical analysis in this study. Result : Among 522 twin pregnancy retrieved from medical record in Hospital USM, 388 of twin pregnancy met the inclusion and exclusion criteria. Two hundred and thirty were randomly selected and included in the study. The overall mean (SD) age for delivery in twins was 29.0 (5.37) years old for all mode of delivery. There were 120 cases (52.38%) were delivered via spontaneous vaginal delivery (SVD) for both twins, 96 cases (41.56%) were delivered by lower segment caesarean section (LSCS) for both twins, and 14 cases (6.06%) were delivered by SVD for first twin and assisted vaginal delivery for second twin (SVD-Assisted VD). The significant factors associated to LSCSLSCS delivery for both twin were age (OR: 1.11, 95%CI 1.03, 1.20, p=0.022), history of spontaneous vaginal delivery (OR: 9.35, 95%CI: 4.01, 21.81, p<0.001), and non cephalic presentation of first twin (OR: 90.69, 95%CI: 18.45, 436.18, p<0.001), while significant factor associated to SVD-Assisted VD mode was type of conception (OR: 8.71, 95%CI: 1.14, 66.46, p=0.037). Conclusion: A caesarean section for both twin was associated with older age of mother, noncephalic presentation of first twin and history of vaginal delivery for mode of delivery. While in SVD- Assisted VD for twin delivery was associated with spontaneous type of conception.